Asymmetric supercapacitor based on an α-MoO3 cathode and porous activated carbon anode materials1. Issue 47 (27th May 2015) - Barzegar, F.; Bello, A.; Momodu, D. Y.; Dangbegnon, J. K.; Taghizadeh, F.; Madito, M. J.; Masikhwa, T. M.; Manyala, N.
<x xml:space="preserve">Abstract</x> Low cost porous carbon materials were produced from cheap polymer materials and graphene foam materials which were tested as a negative electrode material in an asymmetric cell configuration with α-MoO3 as a positive electrode.